The Saccharomyces cerevisiae HSP12 gene is activated by the high-osmolarity glycerol pathway and negatively regulated by protein kinase A - Varela, J. (2014)
The HSP12 gene encodes one of the two major small heat shock proteins of Saccharomyces cerevisiae. Hsp12 accumulates massively in yeast cells exposed to heat shock, osmostress, oxidative stress, and high concentrations of alcohol as well as in early-stationary-phase cells. We have cloned an extended 5'-flanking region of the HSP12 gene in order to identify cis-acting elements involved in regulation of this highly expressed stress gene. A detailed analysis of the HSP12 promoter region revealed that five repeats of the stress-responsive CCCCT motif (stress-responsive element [STRE]) are essential to confer wild-type induced levels on a reporter gene upon osmostress, heat shock, and entry into stationary phase. Disruption of the HOG1 and PBS2 genes leads to a dramatic decrease of the HSP12 inducibility in osmostressed cells, whereas overproduction of Hog1 produces a fivefold increase in wild-type induced levels upon a shift to a high salt concentration. On the other hand, mutations resulting in high protein kinase A (PKA) activity reduce or abolish the accumulation of the HSP12 mRNA in stressed cells. Conversely, mutants containing defective PKA catalytic subunits exhibit high basal levels of HSP12 mRNA. Taken together, these results suggest that HSP12 is a target of the high-osmolarity glycerol (HOG) response pathway under negative control of the Ras-PKA pathway. Furthermore, they confirm earlier observations that STRE-like sequences are responsive to a broad range of stresses and that the HOG and Ras-PKA pathways have antagonistic effects upon CCCCT-driven transcription.